2020
DOI: 10.1016/j.rser.2020.110300
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the potential of citizen-financed community renewable energy to drive Europe's low-carbon energy transition

Abstract: Analysing the potential of citizen-financed community renewable energy to drive Europe's low-carbon energy transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The aim of the EU's efforts is to involve the local community in the energy transformation towards sustainable low-carbon energy. The authors [59] undertook the task of determining the participation of society in the energy transformation towards the RE in Europe. Surveys have shown that the society to a large extent is open to the energy transformation and wants to develop ecological energy sources.…”
Section: Opportunities For the Development Of The Re Sector In Polandmentioning
confidence: 99%
“…The aim of the EU's efforts is to involve the local community in the energy transformation towards sustainable low-carbon energy. The authors [59] undertook the task of determining the participation of society in the energy transformation towards the RE in Europe. Surveys have shown that the society to a large extent is open to the energy transformation and wants to develop ecological energy sources.…”
Section: Opportunities For the Development Of The Re Sector In Polandmentioning
confidence: 99%
“…The FOR loop in (1) scrolls the index t from start to end; in case of over generation, the condition in ( 2) is fulfilled therefore the service capacity 𝑃 𝑖,𝑃𝑉 𝑆𝑒𝑟𝑣 (𝑡) is set equal to the over generation in (3); else, the service capacity is set equal to zero in (5). The PV generation is consequently updated in ( 7) by subtracting the service capacity and the model of the PV-BESS is solved in (8) to calculate the state of charge of the batteries, useful for the next loop, i.e. the time t+1.…”
Section: The Proposed Methods For Calculating the Capacity For An Upward Grid Servicementioning
confidence: 99%
“…Citizen involvement in energy issues and ECs themselves is crucial [4]; in this sense, many efforts are today devoted to showing ordinary people how desirable it is to abandon the position of individuals who manage their own distributed generation to become part of an ENCO [5]. Along this path, studies on social acceptability [6] and institutional preconditions [7] are also underway through extensive surveys and the comprehensive analysis quantifying citizens' potential to co-finance and participate in community renewable energy initiatives across Europe [8]. ECs tend to be local communities; this is because the better adaptation to the legal and regulatory frameworks [9] and the ecosystems diversity [10], the better management of the energy needs and energy consumption as in the case of an urban neighbourhood [11] or a municipality [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, community-based renewable energy unfolding different levels of citizens’ participation and ownership of renewable projects has left the niche status and is assuming a more important role. Renewable energy projects led and financed by citizen can be also considered an innovative medium to bridge the investment gap (Pons-Seres de Brauwer and Cohen 2020 ). At time, Italy is putting efforts to establish an enabling framework for community energy in line with the EU requirements set in the Clean Energy Package.…”
Section: Decentralisation Pathways: Energy Communities and Citizens’ Energymentioning
confidence: 99%